Dhikrullah Vibration as Stimulus of Social Behavior Change - Iskandar Iskandar; Kusumawati Hatta; Azhar Azhar (Budapest International Research and Critics University, 2020)
Dhikrullah is a strong single sound stimulus not yet applied as a stimulus to invite alpha wave in the brain as a center of human consciousness. Dhikrullah has been practiced among Muslims for more than a thousand years, but research on the function of dhikrullah as a stimulus to the brain waves as the center of human consciousness has not yet been completed. Chapter 2 of al-Anfal verse 2 and chapter ar-Rad verse 28. This study is an academic response to the foundation of discovering science for social change through dhikrullah. Scientific attention to behavior change through vibration stimuli is still very few. The combined data in this study consisted of qualitative data from 4 respondents in order to find the Dhikrullah model and quantitative data from 10 subjects to obtain dhikrullah stimulus samples on subject brain waves through Electro Encephalo Graf (EEG). The results obtained by EEG encourage dhikrullah as vibrations to be carried out as a stimulus to brain waves. Dhikrullah through the audiotory nerve is able to stimulate the brain to present alpha waves on the subject while running the dhikrullah. All subjects stated the difficulty of feeling calm during and after dhikrullah as a basis for behavior change. This study is new because it uses EEG to prove that dhikrullah vibration can be a stimulus for behavior change. Behavioral reviewers, especially practitioners can use dhikrullah as a stimulus to help humans who want to get change easily and cheaply.